2018
DOI: 10.1111/joor.12666
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric, muscular and swallowing changes in patients with OSAS

Abstract: Obstructive Sleep Apnoea Syndrome (OSAS) is believed to be associated with craniofacial and neuromuscular changes, although the interplay among these variables still is poorly recognised. The objective of this study was to identify hyoid, muscular and swallowing changes associated with OSAS, and to correlate these alterations with OSAS severity. Cross-sectional study, in a tertiary referral centre. Seventy-two adult individuals participated in this study: 12 controls (without apnoea) and 60 patients with apnoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
0
23
0
2
Order By: Relevance
“…A possible explanation is that the time reduction of the pharyngeal phase reduces the time of one or more events of this phase (UES opening time, for example) what may result in pharyngeal residue. Strengthening this hypothesis, a study revealed that the support time of hyoid bone excursion, considered an important mechanism to maintain UES opening, was significantly shorter in individuals with OSA compared with control group 7 . In addition, considering the GERD risk in this population 38 , researchers point out that the duration of cricopharyngeal muscle relaxation during swallowing, an important mechanism for UES opening 30 , is shorter in individuals with mild GERD compared with individuals without GERD 40 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A possible explanation is that the time reduction of the pharyngeal phase reduces the time of one or more events of this phase (UES opening time, for example) what may result in pharyngeal residue. Strengthening this hypothesis, a study revealed that the support time of hyoid bone excursion, considered an important mechanism to maintain UES opening, was significantly shorter in individuals with OSA compared with control group 7 . In addition, considering the GERD risk in this population 38 , researchers point out that the duration of cricopharyngeal muscle relaxation during swallowing, an important mechanism for UES opening 30 , is shorter in individuals with mild GERD compared with individuals without GERD 40 .…”
Section: Discussionmentioning
confidence: 92%
“…The apnea-hypopnea index (AHI) was calculated as the number of events of apneahypopnea by hour of sleep. OSA severity was defined as mild (AHI: [5][6][7][8][9][10][11][12][13][14], moderate (AHI: 15-30) and severe (AHI >30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the temperature of the submental triangle region (suprahyoid muscle region) can be of clinical interest, as the lower temperatures found in patients with OSA can be associated with the hypofunction of the suprahyoid muscle, 9,35 with consequent reduction in the perfusion of these muscles, and downward positioning of the hyoid bone 9,35 . Another hypothesis for this finding is the slightly higher BMI and neck circumference, associated with a higher fat accumulation in the neck, 36,37 making this region hyporadiant as the high fat tissue acts as an insulating barrier that interferes with heat transfer through the skin and the body's responses to changes in environmental temperature 38 …”
Section: Discussionmentioning
confidence: 99%
“…Some diseases as dentofacial deformities (2) , temporomandibular disorder (3,4) , obstructive sleep apnea (5) have associated orofacial functions impairment.…”
Section: Introductionmentioning
confidence: 99%